Agricultural residues as Precursors for activated carbon production (coconut waste) - Zatil Alyani, Mohd Amin (Universiti Malaysia Perlis, 2009)
Coconut meal and coconut shell were characterized to know the suitability to become the activated carbon precursors. Besides the low cost and decrease the market waste, this attempt was made to produce an alternative activated carbon precursor from the agricultural residue. The effects of different preparation variables which are activation temperature, activation time, carbonization temperature and carbonization time were investigated. Two different gases were used for different processes which was argon gas for carbonization process and CO2 for activation process. Various reaction temperatures were used to get the best temperature for both processes. The optimum temperature for carbonization was 650°C, and for the activation was 800°C. The best time for both of the process was 1 hour. Carbon compositions in both of the samples indicate suitable to make the activated carbon precursors. Furthermore, according to the morphological study, only the coconut shell was really suitable to be the activated carbon compare to coconut meal.